2022
DOI: 10.7759/cureus.30361
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Observational Study on Association of Polypharmacy With Health-Related Quality of Life in Patients With Hypertension

Abstract: IntroductionHypertension is one of the major co-morbidities affecting older Indians, though current trends show that it is increasingly being diagnosed in younger adults as well. In elderly members of the population, it has been shown to be associated with other co-morbidities, making its management difficult. Among the issues that have arisen with its treatment is the increased prevalence of polypharmacy. Thus, there is a need to identify the issues arising from this increase in medications. In particular, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Based on the reports, after adjusting for confounders, more medications were associated with a lower physical component score (PCS), mental component score (MCS), and self-rated health in dialysis patients with multiple symptoms. In India [ 25 ], after adjusting for potential confounders, a study found a negative correlation between the number of medications and the PCS-adjusted score. At the same time, there was a difference of 3.72 points in the unadjusted MCS domain.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the reports, after adjusting for confounders, more medications were associated with a lower physical component score (PCS), mental component score (MCS), and self-rated health in dialysis patients with multiple symptoms. In India [ 25 ], after adjusting for potential confounders, a study found a negative correlation between the number of medications and the PCS-adjusted score. At the same time, there was a difference of 3.72 points in the unadjusted MCS domain.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of this study, polypharmacy was defined as hospitalized COVID-19 cytokine storm patients receiving at least five medications on admission and continuing as such during their hospital stay (8-45 days) [25,26]. Polypharmacy was further classified into major polypharmacy (six to nine medications) and excessive polypharmacy (≥10 medications) [14].…”
Section: Polypharmacymentioning
confidence: 99%
“…This capacity for agility encompasses essential traits such as speed, flexibility, and responsiveness to changes (Baikuni et al, 2022), underscoring the organisation's stability amidst fluctuations. Moreover, the healthcare system includes consistent components, including primary care centres, hospitals, and rehabilitation units that collaborate in difficult, nonlinear ways at various levels, involving patients, families, medical centres, and government entities, sometimes leading to undesired consequences such as adverse treatment reactions or re-hospitalisations (Paramba and Zilate, 2022). This intricacy justifies the implementation of OA as a management criterion in hospital units (Petrick et al, 2023).…”
Section: Introductionmentioning
confidence: 99%